Teams Games Tournament for Collaboration and Learning Motivation in Junior High Science: A Systematic Review - Mohammad Zuly Zulfan Arif; Novi Ratna Dewi; Arif Widiyatmoko; Wiyanto Wiyanto (Universitas Muhammadiyah Sidoarjo, 2026)
The development of 21st-century education requires learning strategies that not only improve academic achievement but also foster essential competencies such as collaboration and learning motivation. However, science learning at the junior high school level is often still dominated by teacher-centered approaches, which limit students’ active participation. Therefore, innovative learning models are needed to create more interactive and engaging learning environments. This study aims to analyze the effectiveness of the Teams Games Tournament (TGT) learning model in improving students’ collaboration skills and learning motivation in junior high school science learning. This research employed a systematic literature review approach using articles obtained from Scopus, Google Scholar, and ERIC databases. The article selection process followed the PRISMA 2020 framework. From an initial identification of 140 articles, 13 relevant studies were selected based on predetermined inclusion and exclusion criteria. The findings suggest that TGT tends to be associated with positive outcomes related to students’ collaboration skills and learning motivation. The integration of cooperative learning and game-based tournament activities encourages active participation, interaction, and engagement in the learning process. Therefore, the TGT model can be considered an effective strategy to support collaborative and motivating science learning at the junior high school level.